2018
DOI: 10.1152/ajpcell.00182.2017
|View full text |Cite
|
Sign up to set email alerts
|

Notch1 regulates endothelial apoptosis via the ERK pathway in chronic obstructive pulmonary disease

Abstract: The Notch signaling pathway plays critical role for determining cell fate by controlling proliferation, differentiation, and apoptosis. In the current study, we investigated the roles of the Notch signaling pathway in cigarette smoke (CS)-induced endothelial apoptosis in chronic obstructive pulmonary disease (COPD). We obtained surgical specimens from 10 patients with COPD and 10 control participants. Notch1, 2, and 4 express in endothelial cells, whereas Notch3 mainly localizes in smooth muscle cells. Compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(76 citation statements)
references
References 39 publications
11
65
0
Order By: Relevance
“…As demonstrated by our previous experiments, CSE treatment signi cantly triggered apoptotic cascade response in HPMECs [4]. By using ow cytometric quantitation of annexin V-propidium iodide staining, we found overexpression of prohibitin prevented apoptosis of HPMECs induced by CSE (Fig.…”
Section: Effect Of Prohibitin Overexpression On Cse Induced Apoptosissupporting
confidence: 73%
See 1 more Smart Citation
“…As demonstrated by our previous experiments, CSE treatment signi cantly triggered apoptotic cascade response in HPMECs [4]. By using ow cytometric quantitation of annexin V-propidium iodide staining, we found overexpression of prohibitin prevented apoptosis of HPMECs induced by CSE (Fig.…”
Section: Effect Of Prohibitin Overexpression On Cse Induced Apoptosissupporting
confidence: 73%
“…Studies conducted in our laboratory have revealed that CSE induce apoptosis in microvescular endothelial cells from lung [3,4]. CSE stimulation may generate ROS, induce DNA damage, leading to oxidative stress and subsequent endothelial cell apoptosis [5].…”
Section: Introductionmentioning
confidence: 99%
“…17 Notch3 is reported to play an important role in regulating the alveolar epithelium. Several of the key functional components in the Notch signaling are downregulated in smokers with COPD including Notch3.…”
Section: Introductionmentioning
confidence: 99%
“…The role of NOTCH in the progression of emphysema in COPD patients is not yet clear. A recent paper showed that NOTCH1/2/4 expression in endothelial cells was downregulated in COPD patients compared to healthy subjects (Zong et al., ). Given that the mouse Notch pathway plays a critical role in controlling apoptosis in endothelial cells (Limbourg et al., ), Notch signaling seems to be a promising key pathway for the progression of emphysema.…”
Section: Notch Signaling In Respiratory Diseasesmentioning
confidence: 99%
“…Given that the mouse Notch pathway plays a critical role in controlling apoptosis in endothelial cells (Limbourg et al., ), Notch signaling seems to be a promising key pathway for the progression of emphysema. The apoptosis of endothelial cells exposed to cigarette smoke extract was alleviated by Notch1 overexpression (Zong et al., ). These results suggest that the downregulation of NOTCH in endothelial cells increases their apoptosis, resulting in emphysema.…”
Section: Notch Signaling In Respiratory Diseasesmentioning
confidence: 99%